Strategi Efektif Pengumpulan Data Asesmen Pembelajaran SD/MI Berbasis Karakter untuk Penguatan Profil Pelajar Pancasila - Alisia Zahro’Atul Baroroh; Nur Khasanah (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2025)
Character-based learning assessment plays a crucial role in shaping the Pancasila Student Profile at the elementary school (SD/MI) level. This study aims to identify effective strategies for collecting character assessment data to ensure that students develop in accordance with Pancasila values. The research methods include analyzing various assessment techniques such as observation, reflection journals, interviews, and scenario-based instruments. Additionally, this study explores the role of teachers, parents, and the school environment in supporting the implementation of character assessment. The findings indicate that effective character assessment must be holistic, involve multiple stakeholders, and be conducted continuously. The main challenges in data collection include time constraints, lack of teacher training in using assessment instruments, and limited use of technology in the assessment process. Therefore, it is recommended that schools adopt a more systematic approach by integrating digital technology, strengthening teachers' capacity through assessment training, and increasing parental involvement in the assessment process. With the right strategies, character assessment can become an effective tool in strengthening the Pancasila Student Profile and shaping a generation that is ethical, independent, and critical-thinking.